Education in Malaysia: development and transformations - Siow, Heng Loke; Hoon, Chang Lee (Symposium Books, 2011)
Education and training have been given priority as part of the preparation for independence as well as in all Malaysia's five-year plans. This chapter reaffirm that education and skills training have been the major instruments for developing the nation's human capital and unifying the various racial groups in nation building through education. This chapter explores the role of education in addressing the development of human capital and national unity in Malaysia as spurred by the Razak Report in 1956. It also traces the key education reforms since Independence in 1957.